Behaviour of the extended modified Volterra lattice -- reductions to generalised mKdV and NLS equations - Wattis, Jonathan A.D.; Gordoa, PIlar; Pickering, Andrew (Elsevier, 2018)
We consider the first member of an extended modified Volterra lattice hierarchy. This system of equations is differential with respect to one independent variable and differential-delay with respect to a second independent variable. We use asymptotic analysis to consider the long wavelength limits of the system. By considering various magnitudes for the parameters involved, we derive reduced equations related to the modified Korteweg-de Vries and nonlinear Schrodinger equations.